RED ONION (Allium ascalonicum) PEEL EXTRACT AS A NATURAL SOURCE OF ANTIOXIDANTS TO ENHANCE THE OXIDATION STABILITY OF REFINED BLEACHED DEODORIZED PALM OIL (RBDPO) - Destia Ayu Prameswari; Dela Retno Maryuni; Saffarina Dini Astari; Salsabila Permata Sari; Desiana Nuriza Putri (Fakultas Teknologi Pertanian Universitas Brawijaya, 2022)
The repeated use of cooking oil can trigger chemical reactions that cause the cooking oil to be unstable to heat. Red onion peel may be an antioxidant because it contains flavonoid compounds, polyphenols, saponins, and alkaloids that scavenge free radicals. This study aims to prove the use of natural antioxidant concentrations of onion peel. This study used a completely randomized design (CRD) consisting of 5 treatments of onion peel extract, namely 3% (P1), 6% (P2), 9% (P3) 12% (P4), without treatment (P-), and the addition of 0,1% BHT (P+) with consecutive times. The ability of antioxidant of onion peel extract is known to be able to maintain the stability of cooking oil compared to an antioxidant synthetic BHT. Peroxide in extract oil 9% (6.65 meq/kg), Total Oxidation in extract oil 9% (15.92 meq/kg), P-anisidine in extract oil 3% and 9% (3.54 meq/kg) /kg and 3.92 meq/kg) and the iodine value of the extract oil 3%, and 9% (21.41 mg iodine/g and 20.81 mg iodine/g). It was found that natural antioxidants of onion peel extract showed better primary oxidation inhibition ability than synthetic antioxidants BHT and among the five types of antioxidant concentrations, antioxidants from onion peel extract 9% showed the best oxidation inhibition ability. So that it can be obtained that the addition of onion peel extract is used as a natural antioxidant to maintain the stability of the oil against heat